GCN5L: a critical target in energy metabolism pathways - Kou, Yushun; Ma, Ruiling; Wang, Yiyuan; Chen, Xiaojie; Li, Bin; Wu, Tao; Gu, Yuanhui; Yi, Lin (Frontiers in Cell and Developmental Biology, 2025)
GCN5L (GCN5-like protein), as a core component of a novel epigenetic-regulatory complex, exerts precise control over mitochondrial metabolic enzyme activity through acetylation modifications. It not only drives energy production but also regulates key processes like lipid metabolism and cellular stress responses. As research on GCN5L advances, exploring its specific regulatory mechanisms and functionality across physiological states has drawn growing interest from researchers. Drawing on 76 studies from CNKI, PubMed, and Web of Science, this review synthesizes current research advances on GCN5L. It aims to elucidate GCN5L’s physiological significance as a critical target in energy metabolism, providing valuable references for related disciplines and advancing both theoretical understanding and practical applications in metabolic regulation.